Who knew? : the wonders of biomimicry - Madden, Kathleen E. (Who knew?, 2024)
"Sometimes nature is the world's greatest innovator. From butterfly wings to kingfisher birds, nature has been inspiring humans to build better and smarter for generations. This introduction to biomimicry is filled with stunning photographs and amazing facts to encourage engagement and spark curiosity in early readers"--